Wallace Nutting : father of the colonial revival movement - Palmer, Linda B., 1946- (New Glarus, WI : CKBooks Publishing, 2020)
Indispensable reading for historians, novice antique collectors, antique connoisseurs, dealers, museums and historical societies. In this book you will learn the many facets of Wallace Nutting: Congregational Minister, Photographer of hand-colored platinum prints, Author, Antique Collector, Historic Preservationist, Reproduction Furniture Maker, Benefactor, Lecturer. David McCullough, our beloved American historian, said, "History is a story." This is the story of Wallace Nutting
Also available in ebook format.
Includes bibliographical references (pages 186-192) and index.
Keywords: Nutting, Wallace, -- 1861-1941.; Nutting, Wallace, -- 1861-1941.; 1900-1999; Furniture, Colonial -- United States -- Reproduction; Congregational churches -- United States -- Clergy; Furniture -- United States -- History -- 20th century; Colonial revival (Art); Néo-colonial (Art); ANTIQUES & COLLECTIBLES -- Furniture; DESIGN -- Furniture; Colonial revival (Art); Congregational churches -- Clergy; Furniture; Furniture, Colonial -- Reproduction; United States; History